(untitled) (Research, Society and Development, 2021)
The present study aimed to investigate the spatial variability of soil penetration resistance (SPR) in cultivation areas of ‘BRS Princesa’ banana, to evaluate its effects on the chemical and physical attributes of the soil and to indicate localized management. The experiment was carried out in an area of cultivation ‘BRS Princesa’ banana, in which 60 georeferenced points were recorded. SPR was measured from the cone index to 0.40 m depth using an impact penetrometer. Disturbed samples were collected at depths of 0-0.05, 0.05-0.10, 0.10-0.20 and 0.20-0.40 m and the soil attributes pH, Ca, Mg, Al, Na, K, P, H + Al, SB, T Value, V%, total sand, total clay, silt, TOC, POC, MAOC and gravimetric moisture were determined. The data were subjected to descriptive statistics, Pearson’s linear correlation and geostatistical analysis. SPR values in subsurface suggest greater compaction in subsurface and the significant correlations with soil attributes indicate losses for banana plants, so localized management should be carried out. It was found that 46.7% of the total area of the banana plantation does not need to be decompacted, and localized subsoiling at a varying depth is indicated in the other regions.